UIKit dynamics playing with physics on iOS - Nugent, Tim; Buttfield-Addison, Paris (O'Reilly, 2017)
"Managing your iOS app's user interface keeps getting easier with Apple's developer tools. This Learning Path focuses on UIKit Dynamics, which provides a way to integrate real-world physics, mechanics, and animation into your app--basically a nifty little physics engine! Learn how to use UIKit dynamics by following Paris, Jon, and Tim as they show how gravity works on a box. Oh, and there's a cool pendulum example as well."--Resource description page.
Title from title screen (viewed April 21, 2017)
Keywords: iOS (Electronic resource); Application software -- Development; Computer animation; Logiciels d'application; Développement; Animation par ordinateur; computer animation; Application software; Development